Changes in humoral immune response after SARS‐CoV‐2 infection in liver transplant recipients compared to immunocompetent patients. Issue 8 (27th April 2021) - Caballero‐Marcos, Aránzazu; Salcedo, Magdalena; Alonso‐Fernández, Roberto; Rodríguez‐Perálvarez, Manuel; Olmedo, María; Graus Morales, Javier; Cuervas‐Mons, Valentín; Cachero, Alba; Loinaz‐Segurola, Carmelo; Iñarrairaegui, Mercedes; Castells, Lluís; Pascual, Sonia; et al.
Abstract : The protective capacity and duration of humoral immunity after SARS‐CoV‐2 infection are not yet understood in solid organ transplant recipients. A prospective multicenter study was performed to evaluate the persistence of anti‐nucleocapsid IgG antibodies in liver transplant recipients 6 months after coronavirus disease 2019 (COVID‐19) resolution. A total of 71 liver transplant recipients were matched with 71 immunocompetent controls by a propensity score including variables with a well‐known prognostic impact in COVID‐19. Paired case–control serological data were also available in 62 liver transplant patients and 62 controls at month 3 after COVID‐19. Liver transplant recipients showed a lower incidence of anti‐nucleocapsid IgG antibodies at 3 months (77.4% vs. 100%, p < .001) and at 6 months (63.4% vs. 90.1%, p < .001). Lower levels of antibodies were also observed in liver transplant patients at 3 ( p = .001) and 6 months ( p < .001) after COVID‐19. In transplant patients, female gender (OR = 13.49, 95% CI: 2.17–83.8), a longer interval since transplantation (OR = 1.19, 95% CI: 1.03–1.36), and therapy with renin–angiotensin–aldosterone system inhibitors (OR = 7.11, 95% CI: 1.47–34.50) were independently associated with persistence of antibodies beyond 6 months after COVID‐19. Therefore, as compared with immunocompetent patients, liver transplant recipients show a lower prevalence of anti‐SARS‐CoV‐2 antibodies and more pronounced antibody levels decline. Abstract : After COVID‐19, liver transplant recipients, compared to immunocompetent patients, exhibit greater decline in antibody levels and lower prevalence of anti‐SARS‐CoV‐2 antibodies at 6 months which is independently associated with female sex, interval since liver transplantation, and treatment with angiotensin‐converting enzyme inhibitors or angiotensin receptor blockers.